Experimental observations of multiple solitons generation in a carbon-nanotube based passively mode-locked fiber laser - Jiang, Kai (2013)
We report the experimental observations of multiple solitons generation from a carbon nanotube (CNT) -based passively mode-locked fiber lasers. After a fiber-connector-type saturable absorber in which CNT is coated on the fiber connector end is successfully fabricated, stable mode-locked pulses with a 18.8MHz fundamental repetition rate at 1568nm central wavelength is self-started with only 12mW pumping power. The dynamic evolution of solitons as a function of the pump power is presented. Our laser produces multiple solitons of up to ten for the pump power of only 60mW.